Intellectual Disability and Multiple Co Morbid Psychiatric Disorders in a Child: A Case Report - Gautam, Priyanka (J Clin Diagn Res, 2014)
Comorbid psychiatric Disorders are seen commonly in people with intellectual disability and in fact they are at greater risk for developing other health disorders. Most prevalent chronic health conditions in children with intellectual disability are epilepsy, cerebral palsy,anxiety disorders, sleep disorders and autism spectrum disorders. Co morbidities multiply the problem of people with intellectual impairment to a great extent and hence an accurate psychological assessment of multiple diagnoses is useful in detecting the specific underlying processes differentiating the co morbid syndrome and in planning an appropriate management and rehabilitation program. This case report is presented to emphasize the fact that though. It is common for intellectually disabled children to have other co-morbid psychiatric disorders, it is important to have accurate, suitable assessment and recording of every co-morbid disorder as it has its own implication in course and outcome of the disability in the child. A comprehensive management approach involving people from various spheres would be required to improve the quality of life and for reduction of burden of care giver.We describe a child of intellectual disability with multiple co morbidities.